Does Authentic Leadership Depend on National Culture? - Furmańczyk, Joanna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The author presents the theoretical assumptions and concepts concerning the cultural determinants of leadership in Japanese and German international enterprises. The author not only describes the theoretical assumptions behind authentic leadership and the links between an organisation and culture, but also presents results of empirical research conducted among 57 top managers of international automotive enterprises operating in Poland. The results show that for German enterprises the strongest correlations were between dimensions of authentic leadership and power distance. In the Japanese enterprises, both power distance and individualism were key in determining the dimensions of authentic leadership.